Characterization of activation induced [18]F-FDG uptake in Dendritic Cells - Pektor, Stefanie; Lawaczeck, Laura; Tenzer, Stephan; Bausbacher, Nicole; Hoffmann, Manuela Andrea; Schreckenberger, Mathias; Miederer, Matthias (Nuklearmedizin - NuclearMedicine, 2020)
Aim Activation of immune cells leads to enhanced glucose uptake that can be visualized by [18]F-Fluorodeoxyglucose ([18]F-FDG) positron emission tomography/computed tomography (PET/CT). Dendritic cells (DC) are essential for the function of the adaptive immune system. In contrast to other immune cells metabolic changes leading to an increase of [18]F-FDG uptake are poorly investigated. Here, we analysed the impact of different DC activation pathways on their [18]F-FDG uptake. This effect was then used to radiolabel DC with [18]F-FDG and track their migration in vivo.Methods DC were generated from bone marrow progenitors (BMDC) or isolated from spleens (SPDC) of C57BL/6 mice. After stimulation with the TLR ligands LPS and CpG or anti-CD40 antibody for up to 72 hours activation markers and glucose transporters (GLUTs) were measured by flow cytometry. Uptake of [18]F-FDG was measured by gamma-counting. DC lysates were analysed for expression of glycolysis relevant proteins by mass spectrometry (MS). [18]F-FDG-labeled DC were injected into footpads of mice to image DC migration.Results BMDC and SPDC showed strong upregulation of activation markers predominantly 24 hours after TLR stimulation followed by higher uptake of [18]F-FDG. In line with this, the expression of GLUTs was upregulated during the course of activation. Furthermore, MS analyses of DC lysates revealed differential regulation of glycolysis relevant proteins according to the stimulatory pathway. As a proof of principle, DC were labeled with [18]F-FDG upon activation to follow their migration in vivo via PET/MRI.Conclusion Immune stimulation of DC leads to enhanced [18]F-FDG uptake into DC, representing the typical shift to aerobic glycolysis in immune cells after activation.
Keywords: dendritic cells; [18]F-FDG uptake; metabolism; glucose transporter; immune system